Evaluation of Grazing Options During Summer for Growing Heifers – Year 3 - Jaymelynn K. Farney; Larissa Muniz; Harley Allen (Kansas Agricultural Experiment Station Research Reports, 2023)
Developing methods to provide high quality forage through most of the year is important for cattle operations. The purpose of this study was to determine forage management options to offset the summer “slump” with fescue. Four grass pasture treatments (10 pastures total; 4 acres each) were used in a completely randomized design and stocked with growing heifers (n = 49; initial wt 461 ± 65 lb). Pasture treatments consisted of novel fescue (FES), crabgrass (CRAB), bermudagrass (BERM), and sorghum-sudan interseeded into novel fescue (SS-FES). Heifers were weighed and they grazed pastures from May to September. Heifers on FES were continuously grazed. All other pastures were rotationally grazed. Sorghum-sudan was interseeded into fescue pastures in May. Average daily gain (ADG) for the entire grazing period was not different between pasture systems. Heifers on BERM and SS-FES had greater gain per acre than those FES pastures, with CRAB being intermediate. This result was primarily based on the increased stocking rates for those pastures. The extreme drought during the summer of 2022 resulted in little to no production of the sorghum-sudan and these pastures had the lowest biomass through the grazing period. Moisture is essential for success of interseeding sorghum-sudan into fescue pastures. Weather patterns impact animal performance as it impacts forage production. The best management practice may involve operations that have a variety of cool and warm-season grasses that producers can use to optimize forage production through varying weather events.
Keywords: sorghum-sudan interseeding; heifer development; Bermudagrass; crabgrass; fescue